(untitled) (Journal of Asian Development Studies, 2024)
The ageing population is on the rise globally. Following retirement, individuals in their old age often rely on others to meet their socioeconomic needs. Nonetheless, the post-retirement ageing experiences of this segment of society, especially women, are underrepresented in the existing literature. The current study investigates the ageing experiences of older women from Lahore, Multan, and Rawalpindi to fill this gap while employing qualitative research methodology. In-depth interviews with older working women produced three themes: work as identity, socio-cultural dynamics, and the challenges of ageing and work. Engaging in work after retirement proved advantageous for maintaining financial independence and fostering active involvement in civic affairs. Nevertheless, these women encountered numerous socio-cultural obstacles. Obstacles operated within the framework of patriarchal norms and generated numerous gender stereotypes. Moreover, older working women articulated that the challenges faced in the workplace and societal and familial expectations frequently oppose their professional drives. Consequently, the author posits that older women can be valuable contributors to the workplace; however, an inclusive environment is essential to inspire their engagement.